Effects of acupuncture for Bell’s palsy patients in the acute phase and its impact on facial nerve edema: a study protocol for a randomized, controlled trial - Wang, Zhidan; Zhang, Jie; Zhang, Zhen; Liu, Yue; Ren, Shuang; Sun, Hao; Meng, Di; Liu, Ruoshi; Zhang, Yang (Frontiers in Neurology, 2024)
Background Bell’s palsy is an acute peripheral facial neuropathy, which is one of the most common causes of facial palsy of lower motor neurons. Facial nerve swelling is commonly observed in Bell’s palsy. Acupuncture therapy has been widely used in the treatment of Bell’s palsy. However, whether acupuncture can be effectively used in the acute stage is still controversial. There are no clinical trials conducted previously to evaluate the effect of acupuncture on facial nerve edema in Bell’s palsy patients. The study aims to evaluate the potential efficacy of different acupuncture modalities on Bell’s palsy patients in the acute phase, its effect on facial nerve edema, and to preliminarily explore its possible mechanism. Methods and analysis In this randomized, controlled trial, 165 Bell’s palsy patients with unilateral onset within 3 days will be recruited and randomly assigned to either the electroacupuncture group (n = 33), the acupuncture group (n = 33), the sham acupuncture group (n = 33), the blank control group (n = 33), or the acupuncture control group (n = 33) in a 1:1:1:1:1 ratio. The participants will receive 4 weeks of treatment and 8 weeks of follow-up. The five groups of participants will receive the following treatments: A: Electroacupuncture + Medication (prednisone acetate tablets, mecobalamin tablets, and vitamin B1 tablets); B: Acupuncture + Medication; C: Sham Acupuncture + Medication; D: Medication only; and E: Acupuncture only. The primary outcome will be the effectiveness rate of different acupuncture modalities in improving facial nerve function after the intervention period. The secondary outcomes will be the recovery speed, the diameter of the facial nerve, the echo intensity and thickness of facial muscles, blood flow parameters of the facial artery, the serum inflammatory level, safety evaluation, and adverse events. Preliminary exploration of its mechanism of action occurs through inflammation and immune response. The difference between groups will be assessed using repeated measure analysis of covariance (ANCOVA) and trend chi-square. Discussion The trial will evaluate the efficacy and facial nerve edema of acupuncture for Bell’s palsy patients in the acute phase and preliminarily explore its possible mechanism. The results thus may provide evidence for clinical application. Clinical trial registration https://www.chictr.org.cn/bin/project/edit?pid=133211, identifier ChiCTR2100050815.